NCEP-ATP III and IDF criteria for metabolic syndrome predict type 2 diabetes mellitus - Sulistiowati, Eva; Sihombing, Marice (Faculty of Medicine, Trisakti University, 2016)
BackgroundSubjects with metabolic syndrome (MetS) have a greater risk for acquiring type 2 diabetes mellitus (type 2 DM). The MetS criteria usually used are those of the National Cholesterol Education Program Expert Panel (NCEP) and Adult Treatment Panel III (ATP III) and of the International Diabetes Federation (IDF). This study aimed to evaluate the modified NCEP-ATP III and IDF criteria as predictor of type 2 DM among subjects with MetS. MethodsA cohort study was conducted among 4240 subjects with MetS. MetS was determined according to the modified NCEP-ATP III and IDF criteria. The study followed up 3324 non-diabetic subjects of the cohort study of non-communicable disease (NCD) risk factors (NCD study) during a 2-year period. Type 2 DM was determined from the diagnosis by health personnel or from fasting blood glucose of ≥126 mg/dL or blood glucose of ≥200 mg/dL, 2 hours after 75g glucose loading. ResultsThe MetS prevalence based on modified NCEP ATP III and IDF criteria in non-DM subjects was 17.1% and 15.6%, respectively. The risk for DM in subjects with MetS using modified NCEP ATP III and IDF criteria was 4.7 (CI 95%: 3.4-6.5) and 4.1 (CI 95%: 3.0-5.7), respectively. ConclusionsBoth MetS criteria can be used as predictors of the occurrence of DM type 2, but the modified NCEP-ATP III is more properly applied than the IDF criteria in subjects with MetS. Screening programs and routine monitoring of MetS components are required for early detection of type 2 DM.